Saccharibacteria as Organic Carbon Sinks in Hydrocarbon-Fueled Communities - Figueroa-Gonzalez, Perla Abigail; Bornemann, Till L. V.; Adam, Panagiotis S.; Plewka, Julia; Révész, Fruzsina; von Hagen, Christian A.; Táncsics, András; Probst, Alexander J. (Frontiers in Microbiology, 2020)
Organisms of the candidate phylum Saccharibacteria have frequently been detected as active members of hydrocarbon degrading communities, yet their actual role in hydrocarbon degradation remained unclear. Here, we analyzed three enrichment cultures of hydrocarbon-amended groundwater samples using genome-resolved metagenomics to unravel the metabolic potential of indigenous Saccharibacteria. Community profiling based on ribosomal proteins revealed high variation in the enrichment cultures suggesting little reproducibility although identical cultivation conditions were applied. Only 17.5% and 12.5% of the community members were shared between the three enrichment cultures based on ribosomal protein clustering and read mapping of reconstructed genomes, respectively. In one enrichment, two Saccharibacteria strains dominated the community with 16.6% in relative abundance and we were able to recover near-complete genomes for each of them. A detailed analysis of their limited metabolism revealed the capacity for peptide degradation, lactate fermentation from various hexoses, and suggests a scavenging lifestyle with external retrieval of molecular building blocks. In contrast to previous studies suggesting that Saccharibacteria are directly involved in hydrocarbon degradation, our analyses provide evidence that these organisms can be highly abundant scavengers acting rather as organic carbon sinks than hydrocarbon degraders in these communities.